Dampak Pendapatan Daerah Dan Belanja Modal Terhadap Kinerja Keuangan Pemerintah Daerah - Carlos Arnold Atmoko; Khairudin Khairudin (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The monetary implementation of local governments can be seen from the financial performance of their government which is a reflection of the level of achievement of performance results which include planned expenditures and regional revenues as measured by indicators that have been directed through a policy or law regulation within a period of financial planning, which can be used as a reference for the government to regulate its regional finances. This study aims to examine the impact of regional income and capital expenditure on financial performance, especially for local governments in Lampung Province in 2017-2019. Information or data that is sampled in this study utilizes secondary data ranging from financial statistics reports to local governments in the Lampung region. The research methods used are: (1) Descriptive Statistics, (2) Classical Assumption Test, (3) Panel data regression model, (4) Model feasibility test (F), (5) Hypothesis Test (T), (6) Coefficient Determination (R2). The results of this study conclude that local revenue has a positive and significant influence on the financial performance of local governments, while capital expenditures have no impact or effect on the financial performance of local governments. This implies that if the original regional income obtained is high, the presentation of the regional government's financial performance will also increase.